2020
DOI: 10.1186/s41936-020-00147-1
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of the Egyptian Scorpion Venom Androctonus Australis: in vitro and in vivo study

Abstract: Background: Scorpion venom contains various biomolecules with potential therapeutic values against different diseases, including cancer. The present study was carried out to assess the antitumor efficacy of Androctonus australis crude venom using both in vitro and in vivo approaches. Methodology: For in vitro assay, the cytotoxic effect of different venom concentrations was determined against HCT116, HepG2, MCF-7, and PC-3 as cancer cell lines and normal WISH cell line. The in vivo assay was carried out by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Cancer‐related anemia is the most common hematological manifestation in patients with cancer and animal cancer models and may worsen with disease progression (Gaspar et al., 2015; M. Liu et al., 2015). Anemia occurring in tumor‐bearing mice is mainly due to a reduction in RBC counts and hemoglobin levels, and this may occur because of hemolytic or myelosuppression (Aravind et al., 2012; Nafie et al., 2020). As shown in Table 2, the whey peptide‐based enteral diet significantly increased the RBC count, HCT, and MCV value ( p < 0.05) and increased HGB value with no significance, which relieved chemotherapy‐related anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer‐related anemia is the most common hematological manifestation in patients with cancer and animal cancer models and may worsen with disease progression (Gaspar et al., 2015; M. Liu et al., 2015). Anemia occurring in tumor‐bearing mice is mainly due to a reduction in RBC counts and hemoglobin levels, and this may occur because of hemolytic or myelosuppression (Aravind et al., 2012; Nafie et al., 2020). As shown in Table 2, the whey peptide‐based enteral diet significantly increased the RBC count, HCT, and MCV value ( p < 0.05) and increased HGB value with no significance, which relieved chemotherapy‐related anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted for the identification of scorpion venoms( 13 22 ). Although most of these were investigated the pharmacological properties of Buthidae scorpion venoms ( 7 , 14 , 15 , 17 , 19 , 23 25 ), some recent studies focused on the identification and characterization of Buthidae scorpion venoms using state-of-the-art devices ( 4 , 26 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on both A.ausralis and L.q. quinquestriatus venom have focused mainly on its channel blocker (K + and Na + ) properties and its therapeutic use ( 14 , 23 , 24 , 31 ). Al-Asmari et al ( 31 ) have conducted an elemental analysis of L.q.…”
Section: Discussionmentioning
confidence: 99%
“…Research on Rhopalurus junceus venom demonstrated the cytotoxic effect of this venom against cancer cell lines of epithelial origin (Dioguardi et al, 2020). Scorpion venom Androctonus Australis has shown that has anti-tumor activity on HCT116, HepG2, MCF-7, and PC-3 as cancer cell lines (Nafie et al, 2020). Lorena Polloni and colleagues reported that Bothrops Pauloensis venom has Antiangiogenic effects on endothelial cells (Polloni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%